Mothersâ Hand washing Practice and Diarrhea Cases in Children under Five in Baleendah, Bandung - Firdaus, M Syafril; Arya, Insi Farisa Desy; Somasetia, Dadang Hudaya (Althea Medical Journal, 2015)
Background: Diarrhea is a disease, especially in children, with high mortality and morbidity rate inÂ developing countries, including Indonesia. Diarrhea can be prevented if people can apply clean and healthyÂ behaviors, especially hand washing. Hand washing is the cheapest, simplest, and the most effective methodsÂ for prevention of diarrhea. The objective of this study is to identify the knowledge, attitude, and practice ofÂ mothersâ hand washing and diarrhea cases in children under five in Baleendah District, Bandung.Methods: A descriptive study was conducted during SeptemberâNovember 2012 to 210 mothers whoÂ had children (ages 12â59 months) in Baleendah using rapid survey technique. The time allocated for eachÂ village was adjusted to the population proportion for each region. The data were analyzed using computerand was represented using frequency distribution.Results: This study showed that the respondents had good level of knowledge and attitude of hand washingÂ (83.8% and 61%, respectively), but only 21% of the respondentsâ practices of hand washing was in goodÂ level. Most of the respondents did not wash their hands according to the 7 steps of correct hand washing.Â Moreover the percentage of children with diarrhea in Baleendah was 43.8% (92 cases) during the study.Conclusions: There should be dissemination of information about the benefit of washing hands with 7Â steps of correct hands washing so that families can practice it and can prevent diarrhea in children underÂ five. [AMJ.2015;2(1):191â8]